O ensino de permacultura na educação do campo: circulação de sentidos entre ciência e experiência - Marilia Carla de Mello Gaia (2015)
In this thesis I investigate the tension between the natural science knowledge and the experience know-how that emerges from life in the field. I tried to understand the ways to approximate the science and experience speeches and extract lessons for my practice as a teacher in the Field Education Degree in Life and Natural Science Entitlement, as well as for my other activities as a teacher and a militant in the Landless Workers Movement (MST). Therefore, I retraced the path of many authors that worked with the Narrative Inquiry. I narrated a set of Permaculture classes in a course for field workers ministered by another MST militant, here called Francisco. Because of the complexity of the discussion and singularity of this research subject, I sought different authors to help me narrate, think and analyze the class version which I present in the text. I open a dialogue about his experience with the one that emerges from my own work. I did my best to create a dialogue between science and experience. Considering the distinction elaborated by Michel Foucault between knowledge and know-how and the characterization of the ways of paradigmatic thoughts and narrative of Jerome Bruner, I established a cutout between the experience know-how and the scientific knowledge which are equally present in the field and in the academy. The Permaculture class narrative was then analyzed through the circulation of science senses and experience among difficult cultures. I used Carlo Ginzburg and Mikhail Bakhtin as references to discuss the cultural circularity. Form the discussion about language, alterity and dialogue developed by Bakhtin and Paulo Freire in different moments and contexts, as well as other authors that inspired themselves in them, such as João Wanderley Geraldi, I discussed some class particularities with Francisco. Boaventura de Sousa Santos also makes himself present in the narrative analyzes by highlighting the need to include the other voices/know-how in the sharing of the worlds meaning. The know-how which emerges from Franciscos life experience refers to lived, heard and shared histories, from different places and forms, throughout his class. The narrative way and scientific-logical cross this same subject, with a greater intensity in the narrative, which brought many elements for the understanding how the know-how from experience work, and how they appear in a classroom in the field. Instead of giving examples to teach, Francisco tells histories. But they are not disconnected or fragmented histories. They were chosen from the rich collection of his lifes experiences, contributing to share a moral, a teaching, to leave an advice. Without prescribing, Francisco always refers to the permacultural principles in his speech. The main point in his class is not the theory about the settleds life and the Permaculture in his life. The theory is present although his class is essentially oriented by practice, compromised with the singularity of each specific reality, without putting aside his Landless, militant and agricultural identity. Franciscos class is characterized by an open happening, as experiences narratives and dialogue and alterity exercises. In the set of classes the centrality of practice, the singular and particular character of his histories and the collective dimension of the subject, were the highlighted points. Through Franciscos voice I capture some advice given by him and then extract some lessons for my work in the Field Education as a militant.